Efektivitas Implementasi Sighat Taklik dalam Perspektif Teori Efektivitas Hukum pada Perkawinan Muslim - Adnan Yahya Siregar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to analyze the effectiveness of the reading of Sighat Taklik, which is an agreement pronounced by the groom after the marriage contract, in shaping the understanding of husband and wife in fostering a household. This study uses the theory of legal effectiveness as an analytical framework. The method used is a qualitative approach with a field research design. The data collection technique was carried out through interviews and observations, while data analysis used inductive methods. The results of the study show that the implementation of Sighat Taklik reading in KUA in Batang Toru District is still not effective. This is due to the inconsistency of law enforcement in offering readings to the bride and groom and the efforts of the headman in its implementation. The inhibiting factors found include low public understanding of the importance of Sighat Taklik, limited time for law enforcement, and the absence of supporting facilities such as structured special programs. On the other hand, there are supporting factors in the form of an adequate legal framework and efforts from law enforcement. Theoretically, this research contributes to the development of legal effectiveness studies by highlighting the gap between legal norms and their implementation in society. Practically, this study recommends the need to strengthen programs, increase socialization, and stronger institutional commitment to increase the effectiveness of Sighat Taklik readings in building legal awareness and responsibility in household life.